Development of agriculture in Brazil, new paradigms and the role of innovation (Research, Society and Development, 2023)
Despite being recent, public policies aimed at rural farmers have played a fundamental role in the growth of the sector throughout the country. The production of these logics has a great impact on Brazilian consumption. With this, the main objective of this study will be to present aspects, through a bibliographical review, of the development of agriculture in Brazil, highlighting the role of Innovation in the sector. For the study, a literature review was carried out with bibliographical research of works already published and indexed in the scientific databases scielo, lilacs and pepsic and bvs-psi indexes, in addition to classic books on agribusiness theory. Currently, the rural environment is still seen as a source of problems, when in fact it can be the bearer of solutions, linked to the offer of employment, income and quality of life, in addition to environmental preservation, which is today one of the main agendas in society, generating diversification of local economies.